2016
DOI: 10.4049/jimmunol.1601006
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Mass Spectrometry To Study Inflammatory Cartilage Degradation and Resulting Interactions with the Complement System

Abstract: Joint diseases are often characterized by inflammatory processes that result in pathological changes in joint tissues, including cartilage degradation and release of components into the synovial fluid. The complement system plays a central role in promoting the inflammation. Because several cartilage proteins are known to interact with complement, causing either activation or inhibition of the system, we aimed to investigate these interactions comprehensively. Bovine cartilage explants were cultured with IL-1α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Among these secretory proteins, CD55, also known as complement decay-accelerating factor, is a specific marker of HS (40). These results are comparable with another proteomics study by Melin et al (6) showing that IL-1a-stimulated bovine cartilage releases intensively more activated C3. In numerous proteomics studies on OA synovial fluid (41)(42)(43), complement components have been deemed primary factors to differentiate OA from the health.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Among these secretory proteins, CD55, also known as complement decay-accelerating factor, is a specific marker of HS (40). These results are comparable with another proteomics study by Melin et al (6) showing that IL-1a-stimulated bovine cartilage releases intensively more activated C3. In numerous proteomics studies on OA synovial fluid (41)(42)(43), complement components have been deemed primary factors to differentiate OA from the health.…”
Section: Discussionsupporting
confidence: 83%
“…It is known that synovitis in OA can be initiated by cartilage breakdown, with the subsequent phagocytosis of debris, and activation of synoviocytes, leading to the formation of an inflaming microenvironment and synovial fluid (5). Interestingly, Melin et al (6) recently found with a quantitative secretome analysis that the cartilage itself represents a major inducer of complement proteins upon IL-1a stimulation. Indeed, monocytes/macrophages and dendritic cells are the primary producers of both IL-1 and TNF in the OA joint, but they have a classical self-containing mechanism with NO-induced apoptosis and/or anergy (7).…”
mentioning
confidence: 99%
“…Joint diseases are typically characterized by inflammatory processes that lead to pathological changes in the articular tissues, including cartilage degradation and the release of components into the synovial fluid [ 15 ]. A number of cytokines appear to induce the expression of VEGF, such as IL-1β, IL-6, prostaglandin E, epidermal growth factor (EGF), and TNF-α [ 16 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Till today, we are unable to achieve engineered cartilage as it is in the human body. Although cartilage has been investigated for many decades, new technologies such as cryo electron microscopy, solid-state NMR and mass spectrometry can be used to deepen our understanding of natural cartilage to reveal the exact components and molecular structure [ 151 , 152 ].…”
Section: Challengesmentioning
confidence: 99%